2015
DOI: 10.1519/jsc.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Post-Effort Chances in C-Reactive Protein Level Among Soccer Players at the End of the Training Season

Abstract: Numerous literature data point out the differences in immunological parameters as a result of physical effort and the relation of those changes to the subject's fitness level. This study was aimed at the assessment of soccer players' condition and adaptation to physical effort based on the changes in C-reactive protein (CRP) blood level. C-reactive protein, total protein, and albumin plasma levels before and after 60-minute-long outdoor running were determined among 16 (8 men and 8 women) soccer players. Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
16
2
Order By: Relevance
“…It is known that all-cause and especially CVD mortality negatively correlate with both cardiorespiratory and muscular fitness levels in adults [67,68]. The research on CRP as the marker of inflammatory status regarding physical activity confirms the anti-inflammatory effects of this protein [50,69]. In another work [69], Phillips et al found that C3 concentrations were positively associated with increasing sedentary behavior and negatively associated with increasing moderate to vigorous physical activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is known that all-cause and especially CVD mortality negatively correlate with both cardiorespiratory and muscular fitness levels in adults [67,68]. The research on CRP as the marker of inflammatory status regarding physical activity confirms the anti-inflammatory effects of this protein [50,69]. In another work [69], Phillips et al found that C3 concentrations were positively associated with increasing sedentary behavior and negatively associated with increasing moderate to vigorous physical activity.…”
Section: Discussionmentioning
confidence: 93%
“…The calculated ratio measures provide further evidence that each form of exercise presents a markedly different stress stimulus (Figure 1). Moreover, only the RSA test caused CRP corrected for plasma volume loss level to increase, while TP and albumin changes were related with post-effort dehydration before a return to baseline values during recovery (Table 3) [50,51]. On the other hand, the lack of a significant decrease in C2 and C4 protein level following the Beep test lends support to an alternative pathway of complement activation [8].…”
Section: Discussionmentioning
confidence: 96%
“…It appears that CRP may not be a useful muscle damage marker for monitoring fatigue and recovery immediately following a soccer match in U-21 players. However, in their study, Kostrzewa-Nowak et al (2015) stated that CRP levels could be a valuable tool to assess the metabolic response to aerobic exercise. Because the post-match infl ammatory response of CRP levels has a 24-hour peak (Ispirlidis et al, 2008), this time-course could be considered as a valuable tool for assessing fatigue in soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in CRP level among the participants in the current study is consistent with the enzymatic profile described above and indicates that the training program caused muscular damage, therefore inducing pro-and anti-inflammatory responses. These responses provide further evidence that CRP is involved in the systematic responses to exercise-induced inflammation [54,55]. These processes stimulate muscular regeneration processes, so it can be considered as a positive effect of realized training program.…”
Section: The Impact Of the Training Program On Biochemical Plasma Promentioning
confidence: 66%